A 60-year-old diabetic patient presented with post coronary artery bypass grafting status with persistent pain and stiffness of left shoulder joint (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below:A 60-year-old diabetic male patient presented with persistent left shoulder joint pain for the last 6 months following coronary artery bypass graft (CABG) surgery. The pain was insidious onset, non-radiating, and dull which aggravated by movement as well as on left lateral position during sleep. However, the pain was not associated with morning stiffness. He had been treated with oral anti-diabetic medications for diabetes mellitus for the last 15 years. However, recently he required to switch to premixed insulin injection for good control of his glycemic status. Apart from post CABG status and diabetes mellitus, he was relatively well and had no other significant medical records like direct trauma over the shoulder joint.